Synthesis of Colloidal Silver Nanoparticles by Reducing Aqueous AgNO3 Using Green Reducing Agents. (2018) - Panda, S.K.; Sen, S.; Roy, S.; Moyez, A.
Abstract: Yellow colour silver nanoparticle (Ag NP)-based colloids have been synthesized by reducing 1mM aqueous AgNO3 using various plant extracts like Ocimum tenuiflorum ( Black tulsi ), Azadirachta indica ( Neem ), Solanum lycopersicum (Tomato), Citrus limon (Lemon), Capsicum annum (Green chilli) and Cucumis sativas (Cucumber). Prepared collidal Ag NPs don't show significant ageing even after a week. Plant extract not only acts as reducing agent but also coats the NPs and provides them stability. Ocimum tenuiflorum extract has been considered as best reducing agent among the plant extracts used for this study to yield dense, fine, spherical and stable colloidal NPs.